Phytophagous Features Of Californian And Purple Scale Insects In The Jujube Agrocenosis - B.E.Murodov; J.N.Yakhyoev (Zien Journals, 2024)
Ten species of diaspid scale insects were studied in the jujube agrocenosis. The identified species were distributed across the following genera: Diaspidiotus (4 species), Salicicola (1 species), Parlatoria (2 species), and Lepidosaphes (3 species).
Keywords: Jujube plant; bioecology; phytophagous; imago